Lulak Abad Iron Occurrence, Northwest of Zanjan: Metamorphosed and Deformed Volcano-Sedimentary Type of Mineralization in Central Iran - Mehri Karami; Mohammad Ebrahimi; Hossein Kouhestani (Journal of Economic Geology, 2016)
Keywords: Iron mineralization, hydrothermal vein, alteration, Lulak Abad, Zanjan, Central Iran